Nutritional evaluation of silage with coffee (Coffea Arabica L.) cherry for ruminant supplementation (2018)
The aim of this study was to evaluate nutritionally coffee cherry (Coffea Arabica L.) silages with different additives: efficient microorganisms (EM) and kumis, to be used in ruminant supplementation. Micro silos were prepared according to treatments: a control treatment with coffee cherry and two experimental treatments with additives (cherry + EM and cherry + commercial kumis). Five fermentation times (1, 8, 16, 21 and 31 days) were evaluated for pH and temperature, and three fermentation times (1, 16 and 31 days) were evaluated for dry matter, protein and neutral detergent fiber; organoleptic indicator evaluation (smell, color and texture) was performed at day 31. A completely randomized design with factorial arrangement was used and linear effects, quadratic and cubic were tested over time using a regression analysis. The results did not show any statistical differences between treatments (P .05) for pH (4.0), temperature values showed highly significant differences (P .01), with an initial temperature of 25.3°C, which stabilized over time at 23.9°C. Dry matter did not show any differences (P .05) among treatments, with similar content (20.6%). Regarding protein, significant differences were found (P .05), being higher for the treatment with kumis (18.1 %) which shows that the additives addition, has a positive effect on the nutritional content. Organoleptic indicators were within the parameters estimated as acceptable for animal feeding.